2022
DOI: 10.1182/bloodadvances.2022007938
|View full text |Cite
|
Sign up to set email alerts
|

International consensus statement on the management of cardiovascular risk of Bruton’s tyrosine kinase inhibitors in CLL

Abstract: Bruton’s tyrosine kinase inhibitors (BTKis) have altered the treatment landscape for chronic lymphocytic leukemia (CLL) by offering effective and well-tolerated therapeutic options. However, since the approval of ibrutinib, concern has risen regarding the risk of cardiovascular (CV) adverse events, including atrial fibrillation (AF), hypertension, and heart failure. Newer BTKis appear to have lower CV risks, but data are limited. It is important to understand the risks posed by BTKis and how those risks intera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 59 publications
1
33
0
1
Order By: Relevance
“…Our findings are in line with consensus guidelines, which suggest that ibrutinib can be safely used in many patients with cardiovascular comorbidities provided these conditions are well controlled and appropriately managed. 18 We further evaluated the relation between baseline covariates known to be associated with cardiovascular disease 29 and the risk for hypertensive outcomes in ibrutinib-treated patients. We observed that both older age and male sex were associated with hypertension.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings are in line with consensus guidelines, which suggest that ibrutinib can be safely used in many patients with cardiovascular comorbidities provided these conditions are well controlled and appropriately managed. 18 We further evaluated the relation between baseline covariates known to be associated with cardiovascular disease 29 and the risk for hypertensive outcomes in ibrutinib-treated patients. We observed that both older age and male sex were associated with hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…A recently published international consensus statement provides guidelines for the monitoring and management of cardiovascular toxicity in patients with CLL who receive treatment with ibrutinib and other BTK inhibitors. 18 We conducted a retrospective analysis of the cardiovascular effects of ibrutinib treatment after 5 years of follow-up on patients with CLL who were included in clinical trials at The University of Texas MD Anderson Cancer Center. The goal of our study was to assess the long-term effects of chronic ibrutinib exposure on blood pressure (BP), the reversibility of this effect upon discontinuation, and the risk of cardiovascular disease and renal complications.…”
Section: Introductionmentioning
confidence: 99%
“…84,116 Overall BTKi have shown dramatically better efficacy across a range of hematological malignancies than traditional chemoimmunotherapies and are well tolerated, however, accumulating data have revealed multiple adverse events, including CVAE. 117…”
Section: Bruton Tyrosine Kinase Inhibitorsmentioning
confidence: 99%
“…121 In addition, ibrutinib has been associated with other cardiovascular toxicities including atrial fibrillation and bleeding; however, next-generation, more selective BTKi (acalabrutinib and zanubrutinib) seem to have an overall lower cardiovascular toxicity, including hypertension. 117 Like ibrutinib, acalabrutinib (second-generation BTKi) was also trialed in refractory CLL patients and similarly demonstrated a treatment-related hypertensive incidence of 7%. 123 However, more recent experience with acalabrutinib from the ELEVATE-TN (Acalabrutinib with or without obinutuzumab versus chlorambucil and obinutuzumab for treatment-naive chronic lymphocytic leukaemia) trial 124 and also the ASCEND (Phase III, randomized trial of acalabrutinib versus idelalisib plus rituximab or bendamustine plus rituximab in relapsed or refractory chronic lymphocytic leukemia) trial 125 suggests lower rates of hypertension, with comparable rates of all-grade and severe-grade hypertension as control treatment groups.…”
Section: Clinical and Epidemiological Evidence For Btki-induced Hyper...mentioning
confidence: 99%
“…Because the FDA label for ibrutinib recently was amended to include a warning regarding fatal and serious cardiac arrhythmias that can occur with ibrutinib therapy, particular attention should be paid to any differences in cardiovascular events that may emerge across combination studies with different generation BTKi partners. Expert recommendations currently counsel physicians to avoid BTKis (particularly ibrutinib) in patients with a history of ventricular arrythmias, 66 thus doublet or triplet therapy with BTKis may not be appropriate for all patients. Further long‐term follow‐up data are required to elucidate the risk of these events with frontline therapy using second‐generation agents, and forthcoming data from larger combination studies (e.g., ACE‐CL‐311) will be of particular interest.…”
Section: Safety Profilementioning
confidence: 99%